Comparative study of immune responses and intestinal microbiota in the gut-liver axis between wild and farmed pike perch (Sander Lucioperca) - Wang, Jing; Li, Shaowu; Sun, Zhipeng; Lu, Cuiyun; Zhao, Ran; Liu, Tianqi; Wang, Di; Zheng, Xianhu (Frontiers in Immunology, 2024)
Introduction Pike perch (Sander Lucioperca) is a predatory freshwater fish, which is highly popular amongst consumers, owing to its white flesh with a delicate structure and mild flavor. Compared to wild pike perch, the diet of farmed ones has shifted from natural food to artificial feeds. These changes would affect the gut flora of the pike perch. Endogenous metabolites of the intestinal flora are transferred through the gut-liver axis, which affects the physiological functions of the host. By studying wild and farmed individuals of the pike perch, novel insights into the stability of the intestinal flora can be provided. Methods and results In this study, we measured various immune parameters in the blood, liver and intestine of wild and farmed pike perch using enzyme activity assays and real-time fluorescence quantitative PCR. Gut microbes were also collected for 16S rRNA gene sequencing. Our results showed that the serum low-density lipoprotein cholesterol (LDL-C) levels were twice as high in the wild group as in the farmed group. Furthermore, the activities of glutamate pyruvate transaminase (GPT) and glutamate oxaloacetate transaminase (GOT) in the intestinal tissues of the wild group were 733.91 U/g and 375.35 U/g, which were significantly higher than those of the farmed group. Expression of IL10 in the liver of farmed pike perch was also 4-fold higher than that of wild pike perch. The expression of genes related to the p53-BAX/Bcl2 signaling pathway was higher in both intestinal and liver tissues of wild pike perch compared with farmed. 16S rRNA gene analysis of the gut microflora showed a high relative abundance of Cetobacterium in the gut of farmed pike perch. Conclusion As a result, our study indicates that dietary differences affect the diversity, composition and relative abundance of the gut flora of the pike perch. Meanwhile, it affects the glycolipid metabolism and immunomodulation of pike perch.